Knowledge about sexual and reproductive health in school-aged adolescents from Mexico - Vera Alanís, Lorena Yuliana; Fernández Fuertes, Andrés A. Fernández-Fuertes (Horizonte Sanitario, 2021)
Objective: To establish a predictive model to estimate knowledge about sexual and reproductive health in schooled adolescents who have not initiated a sexual coital life; for this purpose, the sex and age of the participants in the study will be considered.  Materials and Methods: Correlational descriptive study in 385 students from 12 to 19 years old from Monterrey, Nuevo Leon, Mexico. We applied a personal data card and the Scale of Knowledge, Attitudes and Practices in Sexual and Reproductive Health, which only considered the category of “Knowledge” relating to the dimensions of sexual and reproductive health. Descriptive statistics, chi-square tests (χ²), Pearson correlations and multiple linear regression were carried out, all with a 95% confidence interval.Results: A significant correlation was found between age and knowledge about sexual and reproductive health (r = .382, p < .001). It was also shown that age was the only predictor that is significant for both sexual health knowledge (β = .571 p < .001) and reproductive health (β = .324, p < .001).Conclusions: Many adolescents who took part in this study lack essential knowledge to differentiate between safe and risky sexual behavior. For this reason, in Mexico, it is considered relevant to implement more decisive training actions that guarantee that all adolescents receive comprehensive sexual education, in line with different national and international recommendations.